The knowledge exchange and dissemination plan of the We Can Quit2 community-based stop-smoking trial - Hayes, Catherine (My University, 2021)
We Can Quit2 was a community-based randomised controlled trial which determined the feasibility and acceptability of We Can Quit (WCQ), a peer delivered stop-smoking programme comprising group support and free Nicotine Replacement Therapy (NRT) tailored to women living in socioeconomically disadvantaged areas in Ireland. Reengagement with key stakeholders took place as part of the trial Knowledge Exchange and Dissemination plan, to discuss strategies to optimise community engagement, recruitment and retention in a future definitive trial (DT), and the policy priorities arising from the trial.
European Journal of Public Health
14th European Public Health Conference. Public health futures in a changing world
Keywords: Cancer; Public health